2016
DOI: 10.1111/mam.12059
|View full text |Cite
|
Sign up to set email alerts
|

Bats and aquatic habitats: a review of habitat use and anthropogenic impacts

Abstract: Many bats use aquatic habitats for foraging and for drinking water. Interactions between aquatic and terrestrial systems are important for understanding food web dynamics and for conserving species and ecosystems. Therefore, in this review, I examined the data available on bats’ use of aquatic habitats. The objectives of the present review were to evaluate the importance of aquatic resources for bats and to identify the effects that eutrophication, water pollution, and other anthropogenic impacts on water bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 96 publications
(173 reference statements)
6
43
0
2
Order By: Relevance
“…3). Riparian areas are important habitats for urban bats (Krauel & LeBuhn 2016;Salvarina 2016;Straka et al 2016). Although we were unable to include open water as a variable, our landscape predictions illustrate that it is an important feature on the landscape for bats.…”
Section: Discussionmentioning
confidence: 99%
“…3). Riparian areas are important habitats for urban bats (Krauel & LeBuhn 2016;Salvarina 2016;Straka et al 2016). Although we were unable to include open water as a variable, our landscape predictions illustrate that it is an important feature on the landscape for bats.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic insects can enter the terrestrial landscape, for example, and become a part of its food web. Bats and other terrestrial animals often feed on aquatic insects; thus, water bodies and riparian areas are important habitats for bats (reviewed in Salvarina, ). Water availability has been positively related to bat species richness (McCain, ); therefore, understanding the dependency of bats on aquatic food resources is crucial for conservation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Water availability has been positively related to bat species richness (McCain, ); therefore, understanding the dependency of bats on aquatic food resources is crucial for conservation efforts. Studies that show bat dependence on aquatic resources are more numerous for rivers and streams, than for lakes (36%, 23%, and 17% studies found, respectively, in the total of papers reviewed in Salvarina, ); therefore, lake systems and their importance for bats need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite physiological adaptations for reduced evaporative water loss rates (Muñoz-Garcia et al, 2016), access to free water and roosting are thought to be the main factors driving bat activity and reproductive success in arid environments (Adams & Hayes, 2008;Williams & Dickman, 2004). Yet thus far arid regions have been under-represented in studies examining the use of water resources by bats (Salvarina, 2016).…”
Section: Introductionmentioning
confidence: 99%